Hubungan Pemenuhan Kebutuhan Spiritual Dengan Tingkat Kecemasan Pada Lansia Di Desa Bubunan - Putu Agus Windu Yasa Bukian; Ari Pertama Watiningsih (STIKes Buleleng, 2018)
Introductions : Spirituality is the relationship with the Almighty and the Creator, depending on the beliefs held by individuals. The purpose : Of the study is to find out is there a relationship to fulfillment of spiritual needs with levels of anxiety. Methods : The design of this study was conducted using descriptive correlational research using a cross-sectional approach. Data collection was carried out using the SISRI (The Spiritual Intelligence Self-Report Inventory) questionnaire and HRS-A questionnaire. Result : Correlation test results using the Spearman Rho test get the value of p fulfillment of spiritual needs and anxiety level (0.003) <α (0.05), meaning that. Conclutions : Ho is rejected and Ha is accepted. So it can be concluded that there is a spiritual fulfillment relationship with the level of anxiety of the elderly in the village of Bubunan.